Clinicopathological Predictors of Survival for Parotid Mucoepidermoid Carcinoma: A Systematic Review. (5th February 2023) - Cheng, Emily YiQin; Kim, Joo Hyun; Grose, Elysia M.; Philteos, Justine; Levin, Marc; de Almeida, John; Goldstein, David
Abstract: Objective: Various prognostic factors are associated with the survival of patients with parotid mucoepidermoid carcinoma (MEC). The aim of this systematic review is to summarize the clinical and pathologic prognostic factors on survival outcomes in patients with parotid MEC. Data Sources: Articles published from database inception to July 2020 on OVID Medline, OVID Embase, Cochrane Central, and Scopus. Review Methods: Studies were included that reported clinical or pathologic prognostic factors on survival outcomes for adult patients with parotid MEC. Data extraction, risk of bias, and quality assessment were conducted by 2 independent reviewers. Results: A total of 4290 titles were reviewed, 396 retrieved for full‐text screening, and 18 included in the review. The average risk of bias was high, and quality assessment for the prognostic factors ranged from very low to moderate. Prognostic factors that were consistently associated with negative survival outcomes on multivariate analysis included histologic grade (hazard ratio [HR], 5.66), nodal status (HR, 2.86), distant metastasis (HR, 3.10‐5.80), intraparotid metastasis (HR, 13.52), and age (HR, 1.02‐6.86). Prognostic factors that inconsistently reported associations with survival outcomes were TNM stage, T classification, and N classification. Conclusion: Histologic grade, nodal status, distant metastasis, intraparotid metastasis, and age were associated with worse survival outcomes. These prognostic factors should be considered when determining the most appropriate treatment and follow‐up plan for patients with parotid MEC.